Effect on Heterocyst Differentiation of Nitrogen Fixation in Vegetative Cells of the Cyanobacterium Anabaena variabilis ATCC 29413 - Thiel, Teresa (American Society for Microbiology, 2001)
Heterocysts are terminally differentiated cells of some filamentous cyanobacteria that fix nitrogen for the entire filament under oxic growth conditions. Anabaena variabilis ATCC 29413 is unusual in that it has two Mo-dependent nitrogenases; one, called Nif1, functions in heterocysts, while the second, Nif2, functions under anoxic conditions in vegetative cells. Both nitrogenases depended on expression of the global regulatory protein NtcA. It has long been thought that a product of nitrogen fixation in heterocysts plays a role in maintenance of the spaced pattern of heterocyst differentiation. This model assumes that each cell in a filament senses its own environment in terms of nitrogen sufficiency and responds accordingly in terms of differentiation. Expression of the Nif2 nitrogenase under anoxic conditions in vegetative cells was sufficient to support long-term growth of a nif1 mutant; however, that expression did not prevent differentiation of heterocysts and expression of the nif1 nitrogenase in either the nif1 mutant or the wild-type strain. This suggested that the nitrogen sufficiency of individual cells in the filament did not affect the signal that induces heterocyst differentiation. Perhaps there is a global mechanism by which the filament senses nitrogen sufficiency or insufficiency based on the external availability of fixed nitrogen. The filament would then respond by producing heterocyst differentiation signals that affect the entire filament. This does not preclude cell-to-cell signaling in the maintenance of heterocyst pattern but suggests that overall control of the process is not controlled by nitrogen insufficiency of individual cells.